Enhanced mechanical properties of alkali-activated dolomite dust emulsified asphalt composites - Qun Liu; Weiqing Lin; Lei Xi (Scientific Reports)
Abstract The dolomite dust-emulsified asphalt composite (DAC) with excellent mechanical properties was successfully prepared using alkali activation. The effects of different alkali concentrations and emulsified asphalt contents on the mechanical properties of the materials were studied. And the micro-mechanisms of its mechanical performance changes were analyzed through SEM and XRD characterization. The experimental results show that the specimens have excellent mechanical properties: the 7-day compressive strength can reach 76.67 MPa, and the bending and compressive strength ratio is about twice that of silicate-based geopolymer-emulsified asphalt composite (SAC). With an increase in emulsified asphalt content, the compressive strength of the samples decreases, while the bending strength increases first and then decreases. When the emulsified asphalt content is 1%, the bending strength of the sample is up to 28.81 MPa, which is 25% higher than that of the sample without emulsified asphalt. The in-situ formation of calcium carbonate crystal clusters within the DAC was suggested that may support this performance. This crystalline structuring contributes to an expanded interfacial contact area between the asphalt and skeleton particles, thereby enhancing the demulsification and bonding properties of the emulsified asphalt. This indicates that an appropriate emulsified asphalt content can play a toughening role in the system, providing a new idea for designing high-toughness alkali-activated materials.